Pencucian Uang Dari Perspektif Hukum Pidana Sebagai Follow Up Crime Oleh Korporasi Melalui Pengalihan Dana Ke Dalam Sistem Keuangan - Sibarani, Horison (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
Prevention and eradication of money laundering is very important to maintain national economic stability and prevent previous criminal acts. Law enforcement with strict sanctions is needed so that the prevention and eradication of money laundering can be carried out. This research aims 1) to know and explain the view of positive law on the crime of money laundering as a follow-up crime from the perspective of criminal law 2) to know and explain the efforts to prevent and eradicate the crime of money laundering by corporations transferring funds through the financial system. This research uses a qualitative approach. Legal sources are primary and secondary legal materials. Legal materials are analyzed using descriptive qualitative analysis. The results of the research are money laundering from the perspective of criminal law as a follow-up crime by corporations through the transfer of funds into the financial system. The position of money laundering as a follow-up crime. The complexity in the practice of money laundering makes it very difficult for investigators, public prosecutors to collect evidence, so Law Number 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes requires the burden of proof to the defendant (reverse proof system). The obstacles to the prevention and eradication of money laundering in the corporate environment are weak legal regulations, the complexity of corporate structures, the utilization of financial institutions, the use of large-scale technology, manipulation practices and other factors.